(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
This study presents 27 new host-plants interactions for Agromyzidae established in 19 genera belonging to 8 botanical families. The interactions were established in three natural parks from Eastern Spain on 12 Agromyzidae species: Ophiomyia beckeri (Hendel, 1923); Ophiomyia ononidis Spencer, 1966; Amauromyza (Cephalomyza) flavifrons (Meigen, 1830); Amauromyza (Cephalomyza) karli (Hendel, 1927); Chromatomyia horticola (Goureau, 1851); Liriomyza brassicae (Riley, 1884); Liriomyza bryoniae (Kaltenbach, 1858); Liriomyza cicerina (Rondani, 1875); Liriomyza orbona (Meigen, 1830); Liriomyza trifolii (Burgess in Comstock); Napomyza lateralis (Fallen, 1823) and Pseudonapomyza atratula Zlobin, 2002. Six plant-genera are cited like new hosts for Agromyzidae.